Physicochemical and functional characteristics of starches from common vetch (Vicia sativa L.). (September 2020) - Fu, Liping; Liu, Lu; Chen, Wang; Wang, Qiankun; Lv, Xin; Wang, Jialin; Ji, Zhe; Yu, Guangshui; Liu, Quanlan; Zhang, Xiaodong
Abstract: It is believed that common vetch ( Vicia sativa L.) contains a relatively high quantity of starch. In this study, the starch content of 36 common vetch accessions was monitored, within the range of 20.56–47.53% on a whole seed basis. The amylose content ranged from 17.75 to 38.68% on a dry starch basis. Among them, 8 common vetch accessions were selected for physicochemical and functional analysis, by comparing with 2 smooth pea cultivars and 2 chickpea cultivars. The isolated starches differed significantly in granule morphology, thermal parameters and pasting properties. The shapes of common vetch starch granules were kidney, spherical or oval varied with size from 7.77 to 23.16 μm. The crystalline structures of all starches were C-type. The relative crystallinity of common vetch starches ranged from 22.70 to 34.32% and gelatinization temperature ranged from 63.10 to 66.80 °C. A wider variation of breakdown (BD) (197-910 cp) was observed in common vetch starches than smooth pea and chickpea starches. And the setback (SB) (1314-2221 cP) was lower than that of the pea cultivar P2 and two chickpea cultivars. These could lead common vetch starches to a broad application prospect. Highlights: Common vetch accessions contained higher contents in starch composition. Physical and functional properties of selected common vetch starches were analyzed. Amylose content have great effect on properties of common vetch starches. Great variations in thermal and pasting properties were found in tested starches.